PENGARUH EARNING DAN CASH FLOW OPERATION TERHADAP ARUS KAS MASA DEPAN - Naz'aina Naz'aina; Chairunnisa Chairunnisa (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study is an empirical study that aims to analyze the effect of earning and cash flow operation on future cash flow. The type of data used in this study is secondary data from each companies financial statements in consumer goods sector that listed on Indonesia Stock Exchange in 2014-2018. The number of samples in this study were 27 companies that selected by purposive sampling method. The independent variable used are earning and cash flow operation in 2014-2017, while dependent variable is future cash flow in 2015-2018. The analysis model used in this research is multi linear regression analysis using Eviews 11. 11. The result show that the earning variable has negative and significant effect on future cash flow. The cash flow operation variable has positive and significant effect on future cash flow. Thus, earning and cash flow operation simultaneously have positive and significant effect on future cash flow.